SISTEM INFORMASI KEUANGAN PADA BLOOMING FLOWERS KOTA JAMBI: Information Systems, Transactions, Sales, Services, Rentals - Adriana, Windy (LP2M Universitas Nurdin Hamzah, 2023)
Bouquet rental business is a business in the field of services that is currently developing. Initially the data processing system for leasing is still manual so that it becomes a problem, but along with the increasing number of tenants who make transactions, resulting in greater managed data, thus managing the data by manual method becomes ineffective and inefficient, so as to guarantee accuracy in recording transactions, security in data storage, as well as the accuracy and speed in the presentation of information need to be built a data information system from computer-based bouquets.